Chondroitin Sulphate Proteoglycan Axonal Coats in the Human Mediodorsal Thalamic Nucleus - Pantazopoulos, Harry; Hossain, Nayeem Mubarak; Chelini, Gabriele; Durning, Peter; Barbas, Helen; Zikopoulos, Basilis; Berretta, Sabina (Frontiers in Integrative Neuroscience, 2022)
Mounting evidence supports a key involvement of the chondroitin sulfate proteoglycans (CSPGs) NG2 and brevican (BCAN) in the regulation of axonal functions, including axon guidance, fasciculation, conductance, and myelination. Prior work suggested the possibility that these functions may, at least in part, be carried out by specialized CSPGs structures surrounding axons, termed axonal coats. However, their existence remains controversial. We tested the hypothesis that NG2 and BCAN, known to be associated with oligodendrocyte precursor cells, form axonal coats enveloping myelinated axons in the human brain. In tissue blocks containing the mediodorsal thalamic nucleus (MD) from healthy donors (n=5), we used dual immunofluorescence, confocal microscopy and unbiased stereology to characterize BCAN and NG2 immunoreactive (IR) axonal coats and measure the percentage of myelinated axons associated with them. In a subset of donors (n=3), we used electron microscopy to analyze the spatial relationship between axons and NG2- and BCAN- IR axonal coats within the human MD. Our results show that a substantia percentage (~64%) of large and medium myelinated axons in the human MD are surrounded by NG2- and BCAN- IR axonal coats. Electron microscopy studies show NG2- and BCAN- IR axonal coats are interleaved with myelin sheets, with larger axons displaying greater association with axonal coats. These findings represent the first characterization of NG2 and BCAN axonal coats in the human brain. The large percentage of axons surrounded by CSPG coats, and the role of CSPGs in axonal guidance, fasciculation, conductance and myelination suggest that these structures may contribute to several key axonal properties